2019
DOI: 10.1111/ajt.15419
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric deceased donor kidney transplant outcomes under the Kidney Allocation System

Abstract: The Kidney Allocation System (KAS) has resulted in fewer pediatric kidneys being allocated to pediatric deceased donor kidney transplant (pDDKT) recipients. This had prompted concerns that post‐pDDKT outcomes may worsen. To study this, we used SRTR data to compare the outcomes of 953 pre‐KAS pDDKT (age <18 years) recipients (December 4, 2012–December 3, 2014) with the outcomes of 934 post‐KAS pDDKT recipients (December 4, 2014–December 3, 2016). We analyzed mortality and graft loss by using Cox regression, del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
4
12
2
Order By: Relevance
“…These issues are of particular importance for paediatric recipients who, as a result of excellent long‐term patient survival, require both extended primary graft survival and likely subsequent transplantation. A recent study by Ruck et al 28 in the United States showed that children with 3–6 HLA mismatches had a 43% increased risk of graft failure compared to those with 0–2 mismatches. Despite the introduction of progressive paediatric bonuses in Australia, there has been a gradual increase in mean HLA mismatches for paediatric recipients of deceased donor kidney transplants over the past three decades.…”
Section: Discussionmentioning
confidence: 99%
“…These issues are of particular importance for paediatric recipients who, as a result of excellent long‐term patient survival, require both extended primary graft survival and likely subsequent transplantation. A recent study by Ruck et al 28 in the United States showed that children with 3–6 HLA mismatches had a 43% increased risk of graft failure compared to those with 0–2 mismatches. Despite the introduction of progressive paediatric bonuses in Australia, there has been a gradual increase in mean HLA mismatches for paediatric recipients of deceased donor kidney transplants over the past three decades.…”
Section: Discussionmentioning
confidence: 99%
“…While KAS has led to increased transplant rates for the highly sensitized, racial minorities, and certain blood types in the adult population, 9,[14][15][16] reports of the impact of KAS on the pediatric population have been mixed. [4][5][6]10 Notably, concern over decreased DDKT rates However, kidneys from donors 18-34 years old with KDPI < 35% were 23% less likely to be accepted post-KAS, even after adjusting for donor and recipient characteristics. This might be a consequence of increased selectivity of these high-quality kidneys, since these kidneys were actually 20% more likely to be offered to post-KAS pediatric candidates.…”
Section: Discussionmentioning
confidence: 99%
“…While KAS has led to increased transplant rates for the highly sensitized, racial minorities, and certain blood types in the adult population, reports of the impact of KAS on the pediatric population have been mixed . Notably, concern over decreased DDKT rates for certain pediatric candidates (particularly for candidates ≤6 years old) has led some to suggest that this is the direct result of KAS—that the policy is at fault—and that modifications to KAS should be considered .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of NAT testing, the relatively high prevalence of IVDU and recent concerns about the access of children with ESKD to deceased donor kidneys in the USA [12] combine to make the use of IRD donors a more feasible option to patients, families and clinicians. Declining a kidney from an IRD donor prolongs median waiting time by 9.6 months (11.2 months among those under 6 years of age and 8.8 months among those on dialysis) [13].…”
Section: Nucleic Acid Testingmentioning
confidence: 99%